Poetry and Number in Graeco-Roman Antiquity - Leventhal, Max (Humanities, 2022)
Ranges widely across Greek and Latin poetry to demonstrate the various roles played by number and how the treatment of counting and arithmetic was bound up with wider conceptions of the nature of poetry. Aimed at both classicists and those interested in the cultural history of mathematics.